Effect of lutein on lipid profile in hypercholesterolemic rats - Narayanamurthy, Uma; M., Anandhi; K., Manimekalai (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Hyperlipidemia or Dyslipidemia is the major cause of atherosclerosis1 and associated conditions. Low levels of high-density-lipoprotein cholesterol (HDL-C) are the major causes of increased atherogenic risk 1. Aggressive cholesterol reduction in patients with atherosclerotic disease is now the standard of care2. In addition to life style modification, patients with risk factors need lipid lowering drug therapy. The drugs available now do not reduce LDL oxidation, and oxidative stress associated with hyperlipidemia. In recent years, antioxidants have been subjected to epidemiological studies4 that have related their consumption to a reduction in the incidence of oxidative damage related diseases. Methods: Hypercholesterolemia was induced in rats by administration of high cholesterol diet for 30 days in standard rat chow diet. Rats were divided into four groups of six each. Group-I and II with intake of normal diet and High cholesterol diet respectively. Group III and IV are given high cholesterol diet along with Lutein 50mg/kg and Atorvastatin 5mg/kg orally once daily respectively. At the end of 30 days animals were subjected to overnight fasting. Blood samples were drawn by retro-orbital puncture for biochemical analysis. The animals were sacrificed after thiopentone injection and liver and aorta were dissected out and processed for histopathological study and biochemical analysis. Results: Lutein treated group showed even more significant reduction in TBARS levels than the normal control group and Atorvastatin treated group. The efficacy of Lutein in slowing down the atherosclerosis and fatty infiltration of liver is proved in this study. Conclusions: Hence the present study had shown significant hypolipidemic, antiatherogenic and antioxidant effect of Luetin in Hyperlipidemic rats.